linc00958/miR-185-5p/RSF-1 modulates cisplatin resistance and angiogenesis through AKT1/GSK3β/VEGFA pathway in cervical cancer - Jing Tian; Lei Cheng; Enqi Kong; Wenjin Gu; Yuanyuan Jiang; Quan Hao; Beihua Kong; Li Sun (BMC, 2022)
Abstract Background Chemoresistance is one of the major obstacles that lead to poor prognosis in cervical cancer. linc00958 was reported to be an oncogene in cervical cancer. However, its role in mediating chemoresistance remains to be revealed. Purpose To explore the regulatory mechanisms of linc00958 in cisplatin-resistant cervical cancer cells and further validate in xenograft mice. Methods Online bioinformatic tools were used to conduct the pre-investigation of linc00958/miR-185-5p/RSF-1 and predict the associations between RSF-1 and AKT1/GSK3β/VEGFA in cervical cancer. RT-qPCR measured the RNA expression levels of linc00958/miR-185-5p/RSF-1 in SiHa and SiHa/DDP. Cell survival rates were evaluated by CCK8 methods after cells were exposed to differential concentrations of DDP. Dual-luciferase reporter methods were used to measure luciferase activity. Western blot measured RSF-1 protein and phosphorylated changes of AKT1/GSK3β. Immunofluorescence was employed to observe VEGFA secretion in vitro. Tube formation was applied to evaluate the in-vitro changes of angiogenesis. The SiHa/DDP cells stably transfected with pLKO-sh-NC or pLKO-sh-linc00958 plasmids, were injected into mice, establishing xenograft models. The changes in mice weight and tumor volumes were recorded. H&E staining and Immunohistochemistry (IHC) method was further performed. Results linc00958 expression was higher in SiHa/DDP cells. High linc00958 expression was associated with low overall survival. In SiHa/DDP cells linc00958/miR-185-5p/RSF-1 axis inhibited the cellular resistance to cisplatin and suppressed VEGFA and the tube formation through AKT1/GSK3β/VEGFA pathway. The knockdown of linc00958 inhibited RSF-1 and Ki67, curbing tumor growth; it also inhibited VEGFA and CD34, decreasing angiogenesis in mice. Conclusion linc00958/miR-185-5p/RSF-1 modulates cisplatin resistance and angiogenesis through AKT1/GSK3β/VEGFA pathway in cervical cancer.